Kidney Carbuncle in a Patient with Primary Systemic Al-Amyloidosis and Nephortic Syndrome - A. M. Alieva; M. A. Batov; I. I. Almazova; I. E. Baykova; A. S. Tikhomirova; R. K. Valiev; I. G. Nikitin (Архивъ внутренней медицины, 2021)
The diagnosis and treatment of systemic amyloidosis remains a significant clinical problem for physicians of various specialties. Infectious complications and sepsis account for up to 8% of deaths in amyloidosis patients. This clinical case describes the development of an initially asymptomatic monoclonal gammopathy of unclear significance into systemic AL-amyloidosis, which was complicated by the formation of a renal carbuncle after the first cycles of chemotherapy. There was a significant discrepancy between the severity of the patient’s overall clinical state and changes in laboratory parameters. There were no objective factors for the ascending spread of urinary tract infection or hematogenous dissemination from other foci, so a primary bacteremia was assumed.